Kontribusi Badan Perencanaan Pembangunan Daerah Kabupaten Bima Terhadap Rencana Pembangunan Jangka Menengah Daerah - Arif Budiman; Firmansyah Firmansyah (MIMBAR ADMINISTRASI FISIP UNTAG Semarang, 2023)
The purpose of this study is to determine the contribution of the Regional Development Planning Agency (BAPPEDA) of Bima District in the Regional Medium-Term Development Plan. This research was conducted at the BAPPEDA Office of Bima District. The research subjects were selected through purposive sampling, and the subjects/informants in this research were the Head of BAPPEDA. Data collection techniques consisted of observation, interviews, and documentation. The research results indicate that the implementation of the roles and functions of the Regional Development Planning Agency (BAPPEDA) in the development planning in Bima District can be concluded as follows: the implementation of BAPPEDA functions in Bima District is categorized as not yet good but still sufficient. This means that the implementation of BAPPEDA functions may encounter various obstacles or hindrances in carrying out its functions and programs, which identifies that the implementation of the functions of the Regional Development Planning Agency (BAPPEDA) in development planning in Bima District should always evaluate the implementation.